A comparative statistical analysis of pseudorandom bit sequences - Rashidah Kadir, author; Mohd. Aizaini Maarof, author; International Conference on Information Assurance and Security (5th : 2009 : China) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL